Generative AI Tools for Collaborative Content Creation: A Comparative Analysis - Malakar, Prafull; Leeladharan, M (DESIDOC Journal of Library & Information Technology, 2024)
ICT applications streamlined processes across multiple industries and improved efficiency at a lower cost. Although everyone is generally in favor of this, many people view the development of artificial intelligence as both a blessing and a threat. It is unquestionably widely utilized in academic settings for experimentation and concept articulation, but with so many possibilities available, students and researchers find it difficult to select the best one. This study attempts to evaluate seven generative AI content creation tools—Writesonic, Jasper, Grammarly Business, ProWritingAid, Scalenut, Rytr, and TextCortex AI-using data from the GetApp website. Employing content analysis, the seven selected tools were compared on the basis of qualitative data converted to binary format. Grammarly Business led with a score of (76), followed by Scalenut (75), Writesonic (53), ProWritingAid (51), Jasper (48), TextCortex AI (38), and Rytr (36). This study highlights the pivotal role of collaboration in generative AI, showcasing diverse features, from grammar checks to creative content generation. The significance of this study lies in aiding academia and professionals in strategic tool selection, emphasising the need for informed decision-making in collaborative efforts. Integrating Artificial Intelligence and Natural Language Processing enhances scholarly endeavours, underlining the necessity for efficient content creation during digital evolution.